Pengabdian kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Dusun IV, Desa Tuntungan II, Kabupaten Deli Serdang - Yusnidar Sari Mutiara; Reni Agustina Harahap; Nayla Indah Syaputri; Nanda Fadillah Darus; Mufidah Harahap; Linda Liswana; Yeni Sabariah; Supangge Tiara (Pusat Riset dan Inovasi Nasional, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a community service program integrated into the higher education curriculum, aiming for students to apply theoretical knowledge into real-world practice and contribute to community development and empowerment. This KKN activity was carried out in Dusun IV, Tuntungan II Village, Deli Serdang Regency, from July 1 to August 1, 2025. The main objective of this program was to address various local issues such as limited use of appropriate technology, low environmental awareness, and a lack of human resource development. The method used was field observation to ensure that the programs implemented were in line with the community's needs and potential. Various activities were carried out, including community clean-up (gotong royong), teaching at elementary schools, health counseling for mothers and the elderly, Qur'an recitation lessons for children, compost making, planting a